Dental caries and antemortem tooth loss in Late Antique caucasian Iberia: A bioarchaeological study of Dusheti municipality and Great Mtskheta - Tavartkiladze, Nino (Folia Praehistorica Posnaniensia, 2024)
This bioarchaeological study investigates the prevalence of dental caries and antemortem tooth loss (AMTL) in Late Antique populations of Dusheti municipality and Great Mtskheta in the Caucasus region of Georgia. Dental health data from 75 individuals and 666 examined teeth were analyzed to understand the relationships between dental pathologies, sex, age, and geographical location. Statistical analyses, including chi-square tests, were conducted to assess differences in caries and AMTL frequencies between sexes and regions. The results revealed significant disparities in dental health between Dusheti and Mtskheta, with higher AMTL prevalence observed in Dusheti. Furthermore, age and sex disparities in dental health were identified, with middle-aged adults exhibiting higher AMTL frequency and males demonstrating a higher prevalence of dental caries. These findings highlight the importance of considering historical, socio-economic, and geopolitical factors in understanding oral health outcomes in Late Antique populations. Further interdisciplinary research is recommended to enhance our understanding of oral health dynamics in ancient societies.